STRATEGI PEMBELAJARAN INOVATIF PENDIDIKAN AGAMA ISLAM DENGAN MEDIA POWERPOINT DALAM MENINGKATKAN MUTU PENDIDIKAN DI SDIT MUHAMMADIYAH SINAR FAJAR CAWAS DAN SD MUHAMMADIYAH PK BAYAT - Sigit Trihariyanto; Eko Supriyanto; M Muthoifin; Zahrotul Uyun (Universitas Muhammadiyah Surakarta, 2020)
This research was conducted with the aim of uncovering, analyzing and explaining learning strategies and utilizing PowerPoint media implemented by Islamic religious education teachers in delivering learning materials in the Integrated Islamic Elementary School of Muhammadiyah Sinar Fajar Cawas and the Special Program Elementary School of Muhammadiyah Bayat. This type of research is field research using a qualitative descriptive approach. The data sources and instruments used in this research are observation, interview and documentation study. Based on the research that has been done, the results show that the Integrated Islamic Elementary School of Muhammadiyah Sinar Fajar Cawas and the Special Program Elementary School of Muhammadiyah Bayat have implemented the 2013 curriculum. So that teachers have a very important role in education. Among the teacher roles shown in the two schools were the teacher as a planner, manager, implementer, and evaluator. Also, the teacher plays the role of transferring knowledge, fostering noble morals, mediators and facilitators. In the application of Islamic religious education learning strategies with PowerPoint media in the two schools, they can provide motivation and increase student enthusiasm for learning and learning achievements. In utilizing the strategy, it can make the learning process more attractive, effective, efficient and can help in conditioning students in the learning process and increase confidence for Islamic religious education teachers. As for material delivered using this strategy, it is easier to understand and more practical file storage. Supporting factors in implementing Islamic religious education learning strategies with PowerPoint media in Integrated Islamic Elementary School of Muhammadiyah Sinar Fajar Cawas and Special Program Elementary School of Muhammadiyah Bayat is the ability of teachers to operate computers, the availability of media resources, computer-based facilities, and infrastructure in schools, support from the head school, and the conducive condition of the school environment and the culture of mutual help to help those who are built are quite strong. As for the inhibiting factor is the lack of familiarity of teachers in using PowerPoint media in the learning process, the preparation time is still limited, and the number of computer-based facilities and infrastructure is still limited as well.